PENGARUH VOLUME PRESIPITAT URINE TERHADAP HASIL PEMERIKSAAN SEDIMEN URINE - Kadek Yulinda Damayanti; Putu Ayu Parwati; Mohammad Fairuz Abadi (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2020)
Urinary Tract Infection (UTI) is an infection of the pathogenic microorganisms that thrive in the urinary tract. Urinary Sediment is an examination to determine the presence of abnormalities in the kidneys and urinary tract. Urine precipitate volume is one of the factors that influence urine examination results. The purpose of this research is to determine the effect of urine sediment volume based on the results of urine sediment examination. This type of research is analytic research that use 15 urinary tract infections samples. The results of analysis Kruskal wallis test on leukocytes examination showed p-value <0.05 which showed that there were differences in the number of leukocytes in the three precipitate urine volume comparisons and the results of analysis One Way Anova test on erythrocyte examination showed p-value <0.05 which showed that there were differences the number of erythrocytes in the three urine precipitate volume comparisons. The results of analysis Kruskal Wallis test on crystalline and bacterial examinations obtained p-value >0.05 which showed no differences in the number of crystals and bacteria in the three comparison of urine precipitate volume and the results of analysis One Way Anova test on epithelial cell examination obtained p-value >0.05, which indicates no difference in the number of epithelial cells in the three urine precipitate volume comparisons. Urine sediment examination is expected to use a standard precipitate urine volume of 20 µL.